KAJIAN ETNOBOTANI TUMBUHAN OBAT PADA MASYARAKAT DUSUN SEMONCOL KECAMATAN BALAI KABUPATEN SANGGAU - tria, As; Budhi, Setia; Sisillia, Lolyta (Universitas Tanjungpura, 2013)
The research was conducted at the District Hall Hamlet Semoncol Sanggau . The purpose of this study to determine aspects of ethnobotany of medicinal plant use and knowledge of medicinal plants by local people Semoncol Hamlet . While the benefits of this research can be used as preliminary information on the community didusun Semoncol in utilizing and conserving medicinal plants . Interviews and field research found 33 species of medicinal plants , namely 8 species , 5 types of liana , 8 kinds of herbs , 11 shrubs , and one type of herb . Of the 33 species of medicinal plants , there are 29 species from 21 families have been identified and his family with the scientific name of 87.87 % and the percentage of species that are not found and relatives scientific name is 12.12 % . For most shrubs levels used are 11 species ( 33.33 % ) . Type the ingredients of the most widely used is the sole way which is 30 species ( 90.90 % ) . The most widely used is the leaves which is 20 species ( 60.60 % ) . The most used way of processing is boiled with 15 species ( 45.45 % ) , to how to use the most widely used is the way to drink is 25 species ( 75.75 % ) , for the treatment turned out the way in which treatment is the most widely used 23 species ( 69.69 % ). Keywords : ethnobotany , medicinal plants , people , Sanggau